Incidence and factors associated with the recurrence of Rathke's cleft cyst after surgery: A systematic review and meta-analysis - Qian, Ao; Zhou, Jing; Zhang, Xin; Yu, Jiaojiao; Wang, Xiaoshu (Frontiers in Surgery, 2023)
Backgroud: Recurrence of Rathke’s cleft cyst (RCC) is not uncommon after surgery, and the associated factors and incidence of relapse deserve systematic summary. Methods: This study was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Databases of Pubmed, Embase, Cochrane and Web of science were searched until September 12, 2022. Studies with significant results of recurrent factors or specific incidence of RCC recurrence and mean/median follow-up time were included. Based on a protocol of two-year intervals grouping, included studies were categorized into 4 groups with follow-up period < 24months, 24-48 months, 48-72 months, and ≥ 72 months. Quality assessment was performed using NOS score. Pooled estimations were computed with a random-effects model in the STATA “metaprop” command. Publication bias was assessed visually through funnel plot, and statistically through Egger’s linear regression test and Begg’s correlation test. Results: Total 44 studies were included containing 2539 cases. Squamous metaplasia was the most commonly reported factor, followed by extent of cyst removal. Other factors were reported individually. The pooled overall incidences of RCC recurrence after surgery in 4 groups of follow-up period were 7.4% (95%CI=4.1-11.3%) in < 24 months, 13.1% (95%CI=9.7-17.0%) in 24-48 months, 13.7% (95%CI=7.7-21.0%) in 48-72 months, and 33.8% (95%CI=19.6-49.6%) in ≥ 72 months. The pooled symptomatic incidences were 2.3% (95%CI=0.4-5.1%) in < 24 months, 5.6% (95%CI=3.6-7.9%) in 24-48 months, 5.9% (95%CI=2.4-10.6%) in 48-72 months, and 14.1% (95%CI=6.0-24.5%) in ≥ 72 months. Dramatic increase of recurrent incidence was observed when follow-up period more than 72 months in both overall and symptomatic recurrence. Similar trend of recurrence was also found in subgroup analyses stratified by publication year, cohort size, and cyst resection strategy. Conclusion: This study systematically reviewed recurrent factors and described the profile of trend in RCC recurrent incidence after surgery with follow-up time based on protocol of two-year intervals, finding dramatic increase of recurrent rate with follow-up period more than 72 months that encouraged us to put forward a recommendation of at least 6 years follow-up after surgery for patients with RCC.